Contextual Aspect Of PJBL-Based Physics Module On Planetary Motion In The Solar System For 10TH Grade Students - Firdani, et al. , Febi Navila Ella (International Journal of Educational Sciences and Development, 2023)
Module is a learning material needed by learners to study independently. According to the Buck Institute for Education, PjBL is a teaching method in which learners build understanding of a topic or subject matter through various problem-solving activities, enabling them to enhance learning outcomes and creativity. This study utilized the research and development (R&D) method. The Research and Development method encompasses several types. In this study, the 4-D development model was employed. The results obtained from this research can be concluded as follows: firstly, the PjBL-based module on planetary motion in the solar system for 10th grade, which has been validated by experts. The calculation of expert validation yielded a validator score of 75%, indicating it falls within the category of "appropriate" or "suitable". Therefore, the results obtained from the development of the PjBL-based module on planetary motion in the solar system in Physics indicate that it is appropriate to be used in the teaching and learning process by educators for learners..